YKL-40 Is Associated With Ultrasound-Determined Carotid Atherosclerotic Plaque Instability - Yu Wang (Frontiers in Neurology, 2021)
Background and Aims: YKL-40, an inflammatory biomarker, has been reported to be involved in the process and progression of atherosclerosis. Several studies have investigated the association between YKL-40 and plaque and suggested YKL-40 might be a potential biomarker for plaque instability. This study aimed to investigate the association between YKL-40 and carotid plaque instability.Methods: Based on a community-based study in Beijing from February 2014 to May 2016, 1,132 participants with carotid plaques were enrolled in this study. Data on demographics and medical history were collected through face-to-face interviews, and fasting blood samples were collected and stored. We used ultrasound to evaluate the presence of carotid plaque and its instability. The level of YKL-40 was measured by enzyme-linked immunosorbent assay (ELISA). Multivariate logistic regression analysis was performed to investigate the association between YKL-40 level and carotid atherosclerotic plaque instability.Results: The mean age of the 1,132 participants was 58.0 (52.0–64.0) years, and 560 (49.5%) were male. Unstable plaques were detected in 855 (75.53%) participants. YKL-40 level was classified into four groups according to its quartile: quartile 1: <25.47 ng/mL, quartile 2: 25.47–39.53 ng/mL, quartile 3: 39.53–70.55 ng/mL, quartile 4: ≥70.55 ng/mL. After adjusting for age, sex, smoking, alcohol drinking, medical history, triglycerides, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, homocysteine, high-sensitivity C-reactive protein, and plaque thickness, the top quartiles of YKL-40 level were significantly associated with unstable plaque (quartile 3: OR 2.10, 95% CI 1.29–3.40; quartile 4: OR 1.70, 95% CI 1.04–2.80).Conclusion: This study found that YKL-40 was associated with carotid plaque instability determined by ultrasound. Individuals with high YKL-40 may have a higher risk of unstable carotid plaque.